2011
DOI: 10.1116/1.3567416
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured platforms to study nanotube-mediated long-distance cell-to-cell connections

Abstract: Recently, numerous innovative approaches have attempted to overcome the shortcomings of standard tissue culturing by providing custom-tailored substrates with superior features. In particular, tunable surface chemistry and topographical micro-and nanostructuring have been highlighted as potent effectors to control cell behavior. Apart from tissue engineering and the development of biosensors and diagnostic assays, the need for custom-tailored platform systems is accentuated by a variety of complex and poorly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…1C). Both findings are in consistency with previous observations made for various other cell types [5], [11], [12]. Frequently, discrete filopodia-like protrusions in contact with the substratum and seemingly directed towards adjacent cells, emitted by individual HPMCs were observable (Fig.…”
Section: Resultssupporting
confidence: 93%
“…1C). Both findings are in consistency with previous observations made for various other cell types [5], [11], [12]. Frequently, discrete filopodia-like protrusions in contact with the substratum and seemingly directed towards adjacent cells, emitted by individual HPMCs were observable (Fig.…”
Section: Resultssupporting
confidence: 93%
“…A microgrooved substrate to guide cell alignment has been fabricated to mimic the extracellular matrix topography and explore the virus cell-to-cell spread behavior21. Single PC12 cells have been patterned orderly on biofunctionalized gold microstructures to analyze the influence of cell spacing and alignment to the formation of MNTs22. Optical tweezers on microfluidic chip were used to pull out MNTs23.…”
mentioning
confidence: 99%
“…Furthermore, 3D analysis revealed that nanotubular structures between cells connected at their nearest distance without contact with substrate and were aligned mostly parallel to the substrate surface [22]. The results confirmed that TNTs can span a long distance by hovering in the culture medium without contact with substrate.…”
Section: Resultsmentioning
confidence: 83%
“…TNT is a thin dynamic filopodia-like membrane protrusion connecting surrounding cells over long distances. Different from the structure of filopodia, TNTs have been described as stretched membrane channels between interconnected cells at their nearest distance, meanwhile they hover freely in the cell culture medium and do not contact with the substratum on flat surface [3,22]. However, the extension and connection of TNTs on microstructured surface is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation